The People of the Abyss - London, Jack, 1876-1916 (Salt Lake City, UT : Project Gutenberg, 1999)
"The People of the Abyss" by Jack London is a book published in 1903. It documents London's firsthand experience living among the poor in London's East End slums. Disguising himself and sleeping in workhouses and on streets, the American author immersed himself in the desperate conditions of Whitechapel's working-class. This unflinching account of urban poverty shocked readers and later inspired George Orwell's own investigations into destitution, influencing works like "Down and Out in Paris and London." (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_People_of_the_Abyss
Release date is 1999-03-01
David Price
Keywords: Poor -- England -- London; London (England) -- Social conditions